Femoral and Tibial Bony Risk Factors for Anterior Cruciate Ligament Injuries Are Present in More Than 50% of Healthy Individuals. Issue 14 (December 2021) - Micicoi, Grégoire; Jacquet, Christophe; Khakha, Raghbir; LiArno, Sally; Faizan, Ahmad; Seil, Romain; Kocaoglu, Baris; Cerciello, Simone; Martz, Pierre; Ollivier, Matthieu
Background: Anterior cruciate ligament (ACL) injuries are multifactorial events that may be influenced by morphometric parameters. Associations between primary ACL injuries or graft ruptures and both femoral and tibial bony risk factors have been well described in the literature. Purpose: To determine values of femoral and tibial bony morphology that have been associated with ACL injuries in a reference population. Further, to define interindividual variations according to participant demographics and to identify the proportion of participants presenting at least 1 morphological ACL injury risk factor. Study Design: Cross-sectional study; Level of evidence, 3. Methods: Computed tomography scans of 382 healthy participants were examined. The following bony ACL risk factors were analyzed: notch width index (NWI), lateral femoral condylar index (LFCI), medial posterior plateau tibial angle (MPPTA), and lateral posterior plateau tibial angle (LPPTA). The proportion of this healthy population presenting with at least 1 pathological ACL injury risk factor was determined. A multivariable logistic regression model was constructed to determine the influence of demographic characteristics. Results: According to published thresholds for ACL bony risk factors, 12% of the examined knees exhibited an intercondylar notch width <18.9 mm, 25% had NWI <0.292, 62% exhibited LFCI <0.67, 54% had MPPTA <83.6°, and 15% had LPPTA <81.6°. Only 14.4% of participants exhibited no ACL bony risk factors, whereas 84.5% had between 2 and 4 bony risk factors and 1.1% had all bony risk factors. The multivariate analysis demonstrated that only the intercondylar notch width ( P < .0001) was an independent predictor according to both sex and ethnicity; the LFCI ( P = .012) and MMPTA ( P = .02) were independent predictors according to ethnicity. Conclusion: The precise definition of bony anatomic risk factors for ACL injury remains unclear. Based on published thresholds, 15% to 62% of this reference population would have been considered as being at risk. Large cohort analyses are required to confirm the validity of previously described morphological risk factors and to define which participants may be at risk of primary ACL injury and reinjury after surgical reconstruction.